Modern approach to perioperative pain relief using various modern methods and anesthetics (Pain medicine, 2022)
Adequate postoperative analgesia remains unresolved problem of the acute pain treatment. In spite of wide choice of different groups of analgesics, epidural analgesia is the most adequate and efficient method of the postoperative analgesia. Continuous epidural analgesia is broadly used for postoperative pain relief. Such approach has own advantage over periodic administration of anesthetics into epidural space. These positive effects include constant level of the good pain relief, possibility of patients to participate in process of the pain management, reduction of probability of infectious complications in accordance with the use of epidurals and others. Besides, continues epidural infusion vastly reduces the load on medical stuff. Using electronic pumps for prolonged epidural analgesia has its own advantages and disadvantages. Disposable infusion pumps have not these disadvantages, in contrast of electric infusion pumps. Local anesthetics except their main effect possess anti-inflammatory action. This effect is not only under low plasma concentration, which does not possess cardiotoxic action. Such low plasma concentrations are possible to reach only under prolonged epidural infusion. At present, for prolonged epidural infusion bupivacaine and ropivacaine are most often used. Ropivacain possesses beside advantage over other local anesthetics. Ropivacaine is less cardiotoxic, than bupivacaine.
Keywords: epidural analgesia; single-use infusion pump; ropivacaine; bupivacaine